Characterization of Methicillin resistant Staphylococcus aureus strains from clinical isolates in a tertiary care hospital of south India - Geeta SH; AT Kalghatgi; Rama NK (International Journal of Medical Research and Review, 2015)
Methicillin resistant staphylococcus aureus (MRSA) strains which are the most frequent cause of hospital acquired infections (HAI), are also currently encountered with increasing frequency in the community. Phenotypic detection of methicillin resistance is inadequate, due to environmental factors & heterogeneous resistant strains which may affect the phenotypic expression of resistance. Phenotypic methods for MRSA detection have been compared with the gold standard which is Polymerase Chain Reaction (PCR) for mecA gene. Discrepancies in detection have an adverse effect on patient management, thereby highlighting the importance of accuracy in diagnosis. Therefore rapid & accurate identification is essential for both implementation of infection control measures & prevention of nosocomial spread of the organism.Materials & Methods: 166 S. aureus isolates were studied out of a total of 677 staphylococcal samples. Methicillin resistance were detected using oxacillin disc diffusion (ODD), cefoxitin disc diffusion (CxDD), oxacillin screen agar (OSA) & PCR for mecA gene, using standard protocol.Results: Out of 166 S. aureus isolated, MRSA prevalence was seen in 26.5%. MRSA was identified in 44 (100%) by CxDD, 43 (98%) by OSA and 38 (86.4%) by ODD methods respectively. When these isolates were tested with molecular methods, the CxDD and PCR test results were comparable. However by antibiotic susceptibility test (AST), no strain was resistant to vancomycin, linezolid & teicoplanin.Conclusion: To reduce the prevalence of MRSA, regular surveillance of HAI & monitoring of AST is the need of the hour. Proper detection of all MRSA isolates with rapid & accurate methods must be done as a routine laboratory procedure.